A comprehensive review of BBV152 vaccine development, effectiveness, safety, challenges, and prospects - Dotiwala, Farokh; Upadhyay, Arun K. (Frontiers in Immunology, 2022)
The world has responded to the COVID-19 pandemic with unprecedented speed and vigor in the mass vaccination campaigns, targeted to reduce COVID-19 severity and mortality, reduce the pressure on the healthcare system, re-open society, and reduction in disease mortality and morbidity. Here we review the preclinical and clinical development of BBV152, a whole virus inactivated vaccine and an important tool in the fight to control this pandemic. BBV152, formulated with a TLR7/8 agonist adjuvant generates a Th1-biased immune response that induces high neutralization efficacy against different SARS-CoV-2 variants of concern and robust long-term memory B- and T-cell responses. With seroconversion rates as high as 98.3% in vaccinated individuals, BBV152 shows 77.8% and 93.4% protection from symptomatic COVID-19 disease and severe symptomatic COVID-19 disease respectively. Studies in pediatric populations show superior immunogenicity (geometric mean titer ratio of 1.76 compared to an adult) with a seroconversion rate of >95%. The reactogenicity and safety profiles were comparable across all pediatric age groups between 2-18 yrs. as in adults. Like most approved vaccines, the BBV152 booster given 6 months after full vaccination, reverses a waning immunity, restores the neutralization efficacy, and shows synergy in a heterologous prime-boost study with about 3-fold or 300% increase in neutralization titers against multiple SARS-CoV-2 variants of concern. Based on the interim Phase III data, BBV152 received full authorization for adults and emergency use authorization for children from ages 6 to 18 years in India. It is also licensed for emergency use in 14 countries globally. Over 313 million vaccine doses have already been administered in India alone by April 18th, 2022.